Prevention of Triglyceridemia by (Non-)Anticoagulant Heparin(oids) Does Not Preclude Transplant Vasculopathy and Glomerulosclerosis - Shrestha, Pragyi; Katta, Kirankumar; Talsma, Ditmer; Naggi, Annamaria; Hillebrands, Jan-Luuk; Sluis, Bart van de; van den Born, Jacob (Frontiers in Cell and Developmental Biology, 2022)
Background: In renal transplantation, Chronic Transplant Dysfunction (CTD) is associated with increased PCSK9 and dyslipidemia. PCSK9 is an enzyme that increases plasma cholesterol levels by down-regulating LDLR expression. We recently showed increased PCSK9–syndecan-1 interaction in conditions of proteinuria and renal function loss. Treatment with heparin(oids) might be a therapeutic option to improve dyslipidemia and CTD. We investigated the effects of (non-)anticoagulant heparin(oids) on serum lipids, syndecan-1 and PCSK9 levels and CTD development. Methods: Kidney allotransplantation was performed from female Dark Agouti to male Wistar Furth recipients. Transplanted rats received daily subcutaneous injections of saline, unfractionated heparin, RO-heparin or NAc-heparin (2mg heparin(oid)/kg BW) until sacrifice after 9 weeks of treatment. Results: Saline-treated recipients developed hypertension, proteinuria, and loss of creatinine clearance, (all p<0.05 compared to baseline), along with glomerulosclerosis and arterial neointima formation. Saline-treated recipients showed significant increase in plasma triglycerides (p<0.05), borderline increase in non-HDLc/HDLc (p=0.051), ̴10-fold increase in serum syndecan-1 (p<0.05), without significant increase in serum PCSK9 at 8 weeks compared to baseline. Heparin and non-anticoagulant RO-heparin administration in transplanted rats completely prevented increase in triglycerides compared to saline treated recipients at 8 weeks (both p<0.05). Heparin(oids) treatment did not influence serum total cholesterol (TC), plasma syndecan-1 and PCSK9 levels, creatinine clearance, proteinuria, glomerulosclerosis and arterial neointima formation, 8 weeks after transplantation. Combining all groups, increased syndecan-1 shedding was associated with TC (r=0.5; p=0.03) and with glomerulosclerosis (r=0.53; p=0.021), whereas non-HDLc/HDLc ratio associated with neointima score in the transplanted kidneys (r=0.65; p<0.001). Conclusion: Prevention of triglyceridemia by (non)anticoagulant heparin(oids) neither influenced PCSK9/syndecan-1, nor precluded CTD, which however did associate with shedding of lipoprotein clearance receptor syndecan-1 and unfavorable cholesterol profile.